Impact of plaque burden and composition on coronary slow flow in ST-segment elevation myocardial infarction undergoing percutaneous coronary intervention: intravascular ultrasound and virtual histology analysis. Issue 6 (3rd September 2021) - Reddy, Sreenivas; Rao K, Raghavendra; Kashyap, Jeet Ram; Kadiyala, Vikas; Reddy, Hithesh; Malhotra, Samir; Daggubati, Ramesh; Kumar, Suraj; Soni, Hariom; Kaur, Naindeep; Kaur, Jaspreet; Ramalingam, Vadivelu
Abstract: Aim: Coronary slow flow (SF) is an important complication of percutaneous coronary intervention (PCI) associated with poor prognosis. The aim was to assess grey-scale intravascular ultrasound (IVUS) and virtual histology (VH-IVUS) characteristics of culprit lesion in ST-elevation myocardial infarction (STEMI). Methods: A total of 295 consecutive patients with STEMI underwent coronary angiogram and IVUS. Following PCI, patients divided into two groups; SF (thrombolysis in myocardial infarction [TIMI] flow  ≤ 2, n  = 74) and normal flow (NF) (TIMI flow >2, n  = 221). Coronary plaque burden and its composition in relation to SF were evaluated. Results: On grey-scale IVUS, the plaque area (12.3 mm 2 vs. 11.5 mm 2, p  = .01), plaque volume (110.7 mm 3 vs. 99.8 mm 3, p  < .001), lesion external elastic membrane (EEM) cross-sectional area (14.9 mm 2 vs. 14.0 mm 2, p  = .011) and remodelling index (1.3 vs. 1.2, p  = .043) were significantly higher in SF group. On VH-IVUS, absolute fibrous volume (48.1 mm 3 vs. 41.5 mm 3, p  ≤ .001), fibrofatty volume (23.8 mm 3 vs . 18.6 mm 3, p  = .015), necrotic core volume (8.3 mm 3 vs. 5.5 mm 3, p  < .001), dense calcium volume (1.2 mm 3 vs. 0.6 mm 3, p  = .003) and thin cap fibroatheroma either single (30.1% vs. 16.1%, p  < .001) or multiple (9.6% vs. 1.8%, p  < .001) were higher in SF arm. In multivariable analysis, absolute necrotic core volume (odds ratio  =  1.159; 95% CI 1.030–1.305, p  = .015) was the only independent predictor of SF. Conclusions: Higher necrotic core volume as detected by VH-IVUS may be a potential risk factor for the development of coronary SF phenomenon in patients with STEMI after PCI.